2020
DOI: 10.1099/jgv.0.001441
|View full text |Cite
|
Sign up to set email alerts
|

miR-927 has pro-viral effects during acute and persistent infection with dengue virus type 2 in C6/36 mosquito cells

Abstract: Dengue virus (DENV) is an important flavivirus that is transmitted to humans by Aedes mosquitoes, where it can establish a persistent infection underlying vertical and horizontal transmission. However, the exact mechanism of persistent DENV infection is not well understood. Recently miR-927 was found to be upregulated in C6/36-HT cells at 57 weeks of persistent infection (C6-L57), suggesting its participation during this type of infection. The aim of this study was to determine the role of miR-927 during infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Overexpression or suppression of a miRNA is the most widely used approach to study causality ( Jones-Rhoades et al., 2006 ). Eighteen miRNAs have been validated to exert promotive or inhibitory effects on CHIKV ( Maharaj et al., 2015 ; Dubey et al., 2019 ), DENV ( Hussain et al., 2013 ; Zhang et al., 2013 ; Yan et al., 2014 ; Zhou et al., 2014 ; Su et al., 2017 ; Su et al., 2019 ; Avila-Bonilla et al., 2020 ), WNV ( Slonchak et al., 2014 ), Plasmodium ( Jain et al., 2014 ; Dennison et al., 2015 ; Lampe et al., 2019 ; Dong et al., 2020 ), Wolbachia ( Hussain et al., 2011 ; Zhang et al., 2014 ), or JEV ( Yang et al., 2016 ) infections via these types of experiments ( Table 7 ). Notably, miR-2940-5p restricts the replication of both WNV and DENV in mosquitoes ( Zhang et al., 2013 ; Slonchak et al., 2014 ), and miR-375-3p exerts the opposite effect on DENV-2 and CHIKV ( Hussain et al., 2013 ; Maharaj et al., 2015 ).…”
Section: Advances At Each Step Of the Research Roadmapmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression or suppression of a miRNA is the most widely used approach to study causality ( Jones-Rhoades et al., 2006 ). Eighteen miRNAs have been validated to exert promotive or inhibitory effects on CHIKV ( Maharaj et al., 2015 ; Dubey et al., 2019 ), DENV ( Hussain et al., 2013 ; Zhang et al., 2013 ; Yan et al., 2014 ; Zhou et al., 2014 ; Su et al., 2017 ; Su et al., 2019 ; Avila-Bonilla et al., 2020 ), WNV ( Slonchak et al., 2014 ), Plasmodium ( Jain et al., 2014 ; Dennison et al., 2015 ; Lampe et al., 2019 ; Dong et al., 2020 ), Wolbachia ( Hussain et al., 2011 ; Zhang et al., 2014 ), or JEV ( Yang et al., 2016 ) infections via these types of experiments ( Table 7 ). Notably, miR-2940-5p restricts the replication of both WNV and DENV in mosquitoes ( Zhang et al., 2013 ; Slonchak et al., 2014 ), and miR-375-3p exerts the opposite effect on DENV-2 and CHIKV ( Hussain et al., 2013 ; Maharaj et al., 2015 ).…”
Section: Advances At Each Step Of the Research Roadmapmentioning
confidence: 99%
“…Bioinformatic analysis tools, such as TargetScan, PITA and RNAhybrid, are always used for target prediction. The verification methods usually include the transfection of miRNA-specific antagomirs into mosquito cells, miRNA mimic/inhibitor microinjection in mosquitoes, real-time quantitative polymerase chain reaction (qRT-PCR ) , or luciferase assays ( Liu B. et al., 2016 ; Ma et al., 2017 ; Nouzova et al., 2018 ; Yen et al., 2019 ; Avila-Bonilla et al., 2020 ; Fu et al., 2020 ). The most recent method applied to elucidate the targets and biological functions of mosquito miRNAs is high-throughput sequencing of covalent ligation of endogenous Argonaute-bound RNAs isolated by crosslinking and immunoprecipitation (CLEAR-CLIP).…”
Section: Advances At Each Step Of the Research Roadmapmentioning
confidence: 99%
“…Finally, miR-927 can promote replication of the virus in C6/36 mosquito cells during acute and persistent infection with DENV-2 ( Avila-Bonilla et al, 2020 ). A double luciferase gene reporter experiment confirmed that Filamin (FLN) is a direct target of miR-927 and that FLN is essential in actin rearrangement and related to the regulation of the toll pathway ( Avila-Bonilla et al, 2020 ).…”
Section: The Role Of Mirna In Regulating Denv and Related Signaling Pathwaysmentioning
confidence: 99%
“…Finally, miR-927 can promote replication of the virus in C6/36 mosquito cells during acute and persistent infection with DENV-2 ( Avila-Bonilla et al, 2020 ). A double luciferase gene reporter experiment confirmed that Filamin (FLN) is a direct target of miR-927 and that FLN is essential in actin rearrangement and related to the regulation of the toll pathway ( Avila-Bonilla et al, 2020 ). Several studies have demonstrated that the Toll pathway plays an essential role as an anti-DENV mechanism in both A. aegypti mosquitoes ( Xi et al, 2008 ; Luplertlop et al, 2011 ) and mosquito cells ( Sim and Dimopoulos, 2010 ).…”
Section: The Role Of Mirna In Regulating Denv and Related Signaling Pathwaysmentioning
confidence: 99%
“…In this review we raise some key questions ( Box 1 ), we primarily discuss the Piwi protein and Piwi-interacting RNA (piRNA) pathways in these two Dipteran lineages and we touch upon the endogenous small interfering RNA (endo-siRNA), a canonical branch of RNAi. Although the microRNA (miRNA) branch of the RNAi pathway critically regulates gene expression during development for all animals [ 19 , 20 ], the role of microRNAs in transposon or virus suppression in insects has been more limited to a few studies [ 21 , 22 , 23 ], or has courted controversy [ 24 , 25 , 26 ]. We refer to [ 27 ] for further reading on this topic.…”
Section: Introductionmentioning
confidence: 99%